2018
DOI: 10.3389/fcvm.2018.00179
|View full text |Cite
|
Sign up to set email alerts
|

The Role of G Protein-Coupled Receptors in the Right Ventricle in Pulmonary Hypertension

Abstract: Pressure overload of the right ventricle (RV) in pulmonary arterial hypertension (PAH) leads to RV remodeling and failure, an important determinant of outcome in patients with PAH. Several G protein-coupled receptors (GPCRs) are differentially regulated in the RV myocardium, contributing to the pathogenesis of RV adverse remodeling and dysfunction. Many pharmacological agents that target GPCRs have been demonstrated to result in beneficial effects on left ventricular (LV) failure, such as beta-adrenergic recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 222 publications
(224 reference statements)
0
18
0
Order By: Relevance
“…The focus of this review is on the molecular mechanisms that may contribute to maladaptive remodeling in the RV. Although many pathways are currently under study in the pathogenesis of RV failure (13)(14)(15), this review will specifically focus on select molecular events and pathways that are supported by strong pre-clinical and human (clinical) data that have resulted in, or will lead to, clinical trials in PAH patients.…”
Section: Review Article On Right Ventricular Dysfunctionmentioning
confidence: 99%
“…The focus of this review is on the molecular mechanisms that may contribute to maladaptive remodeling in the RV. Although many pathways are currently under study in the pathogenesis of RV failure (13)(14)(15), this review will specifically focus on select molecular events and pathways that are supported by strong pre-clinical and human (clinical) data that have resulted in, or will lead to, clinical trials in PAH patients.…”
Section: Review Article On Right Ventricular Dysfunctionmentioning
confidence: 99%
“… 9 However, the roles of ET-1 and its receptors in the pathogenesis of RV remodeling are poorly understood. 11 Macitentan is a dual ERA developed by modifying the chemical structure of bosentan to increase safety and efficacy, 12 which displays sustained receptor binding capacity and better tissue penetration. 13 The phase III clinical trial SERAPHIN showed that macitentan reduces morbidity and mortality, with improving pulmonary hemodynamics and 6-min walk distance (6MWD).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mTORC1 is upregulated in right ventricle (RV) myocardium from rats with severe experimental PH and contributes to cardiomyocyte hypertrophy (16). Although prostanoid receptors and PKA play important roles in RV remodeling (17), the role of DP1 in the right heart is not well studied, and a potential link between DP1 and mTORC1 in the hypertrophic RV response to PAH remains to be determined.…”
mentioning
confidence: 99%